2021
DOI: 10.3390/jmse9121416
|View full text |Cite
|
Sign up to set email alerts
|

Application of the IMO Second Generation Intact Stability Criteria to a Ballast-Free Containership

Abstract: A methodology is presented to systematically modify the hull shape of a ballast-free container ship, in order to manage the issue of righting lever variation in waves. The IMO second generation intact stability criteria have been identified as a stability performance assessment tool, while the vertical prismatic coefficient has been selected as the leading parameter of hull modifications to carry out the sensitivity analysis. A revised Lackenby procedure has been chosen to make systematic changes at the hull f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Area (A) under the righting arm curve A0-30° ≥ 0.055 m⋅rad A0-40° ≥ 0.090 m⋅rad A30-40° ≥ 0.030 m⋅rad Righting arm (GZ) GZφ ≥ 30° ≥ 0.20 m Angle corresponding to the maximum of the righting arms φ GZmax ≥ 25° Initial metacentric height (GM) GM ≥ 0.15 m The weather criterion, where a and b are surface areas in the figure below, is based on: [17] b ≥ a List of the ship under static wind pressure perpendicular to the plane of symmetry φ0 ≤ 16° or φ0 ≤ 0.8° φdeck edge entering the water These criteria are mandatory for all ships covered by the SOLAS Convention or the Load Line Convention. For some ships, classification societies may recommend increasing certain requirements [2,18,19]. For example, the initial metacentric height in the loading condition with containers on deck shall not be less than 0.15 m, but the Polish Register of Shipping recommends that this height should not be less than 0.20 m [20].…”
Section: Criterion Requirementmentioning
confidence: 99%
“…Area (A) under the righting arm curve A0-30° ≥ 0.055 m⋅rad A0-40° ≥ 0.090 m⋅rad A30-40° ≥ 0.030 m⋅rad Righting arm (GZ) GZφ ≥ 30° ≥ 0.20 m Angle corresponding to the maximum of the righting arms φ GZmax ≥ 25° Initial metacentric height (GM) GM ≥ 0.15 m The weather criterion, where a and b are surface areas in the figure below, is based on: [17] b ≥ a List of the ship under static wind pressure perpendicular to the plane of symmetry φ0 ≤ 16° or φ0 ≤ 0.8° φdeck edge entering the water These criteria are mandatory for all ships covered by the SOLAS Convention or the Load Line Convention. For some ships, classification societies may recommend increasing certain requirements [2,18,19]. For example, the initial metacentric height in the loading condition with containers on deck shall not be less than 0.15 m, but the Polish Register of Shipping recommends that this height should not be less than 0.20 m [20].…”
Section: Criterion Requirementmentioning
confidence: 99%
“…The level 1 assessment considers two measures of stability: the minimum GM, GM min and a displaced volume ratio. The GM min is computed according to Equation (13), where KB is the metacentric height, I TL is the transverse moment of inertia of the waterplane at the draft d L , ∇ is the displaced volume, and KG is of course the vertical center of gravity above the keel. The draft d L is an average draft between the condition draft and the maximum draft, which is specified in the guidelines.…”
Section: Pl Levelmentioning
confidence: 99%
“…Many researchers have published studies on the application of the criteria to various ship types, which can be found in [6,7,[10][11][12], but most of these studies focus on the dead ship, pure loss, and parametric roll failure modes. In general, few studies have considered all five failure modes in unison, but some examples exist [13]. Excessive acceleration was considered based on early methods in [6], showing the methods were not yet well-developed for general usage, and more recently in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Petacco et al 11 conducted a systematic modification of the hull shape to satisfy the SGIS criteria. The vertical prismatic coefficient was selected as the leading parameter of hull variations, and it was shown that the modified ship satisfied the criteria, whereas the original hull was vulnerable to the parametric roll and pure loss of stability failure modes.…”
Section: Introductionmentioning
confidence: 99%